Morphological and physiological response of two populations of Quercus ilex L. to SO2 fumigation - Infante, J M; Garcia-Laureano, R; Merino, J (PHYTON-ANNALES REI BOTANICAE, 2002)
Quercus ilex L., is the predominant evergreen schlerophyllous tree in the Mediterranean landscape of the Iberian Peninsula. Fruit acorns were collected in two populations located in the center (southern Spain) and at the northern border (northern Spain; a distance of 800 km) of the distribution area of Quercus ilex. One-month-old potted plants were grown for 130 days to a high SO2 concentration (0.23 ppm, 14 h d(-1)) under controlled climate conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: air pollution; Mediterranean ecosystems; Populations; Quercus ilex; Sulfur Dioxide